Potential role of inanimate surfaces for the spread of coronaviruses and their inactivation with disinfectant agents - Günter Kampf (Elsevier, 2020)
Summary: The novel human coronavirus SARS-CoV-2 has become a global health concern causing severe respiratory tract infections in humans. Human-to-human transmissions have been described, probably via droplets but possibly also via contaminated hands or surfaces. In a recent review on the persistence of human and veterinary coronaviruses on inanimate surfaces it was shown that human coronaviruses such as Severe Acute Respiratory Syndrome (SARS) coronavirus, Middle East Respiratory Syndrome (MERS) coronavirus or endemic human coronaviruses (HCoV) can persist on inanimate surfaces like metal, glass or plastic for up to 9 days. Some disinfectant agents effectively reduce coronavirus infectivity within 1 minute such 62%-71% ethanol, 0.5% hydrogen peroxide or 0.1% sodium hypochlorite. Other compounds such as 0.05%-0.2% benzalkonium chloride or 0.02% chlorhexidine digluconate are less effective. An effective surface disinfection may help to ensure an early containment and prevention of further viral spread. Keywords: Coronavirus, Persistence, Inanimate surfaces, Chemical inactivation, Biocidal agents, Disinfection